Carbon Paste Electrode-Modified Imprinted Zeolite X and Its Performance as a Potentiometric and Voltammetric Sensor for Cholesterol Analysis - Khasanah, Miratul; Widati, Alfa Akustia; Severia, Nadya Maya; Oktaviana, Citra Marantika Nur; Puspitasari, Evrillia; Ummah, Naftalia Wirdatul; Alviani, Ziana (Universitas Gadjah Mada, 2025)
Carbon paste electrode-modified imprinted zeolite X has been developed as a potentiometry and voltammetry sensor to monitor cholesterol levels in the body. This is crucial to detect early health risks caused by high cholesterol levels. The modified electrode was fabricated with a mass ratio of activated carbon, paraffin, and imprinted zeolite X of 12:7:1. Potentiometric measurement produced a linear dynamic range of 10−6–10−3 M, Nernst factor of 27.12 mV/decade, a detection limit of 1.12 × 10−6 M, precision of 99.7% (n = 3), and accuracy of 99.8% (n = 5). Using the electrode for up to 56 measurements over 6 weeks did not significantly decrease its performance. The presence of glucose did not interfere with cholesterol analysis by potentiometry. The modified electrode was applied to analyze cholesterol voltammetrically at the optimum deposition potential of 0.4 V, deposition time of 60 s, and a scan rate of 100 mV/s. Voltammetric analysis of cholesterol resulted in a detection limit of 7.2 mg/L (1.86 µM), precision of 96–99%, accuracy of 74–114%, sensitivity of 7.1 nA.L/mg/cm2, and recovery of 87.2% (n = 3). The glucose and urea in various concentrations cause less than 5% current deviations.